Sosialisasi Cara Produksi Pangan Olahan yang Baik pada Pengrajin Tempe Dage di Desa Ciberung, Ajibarang Banyumas - Ajeng Dyah Kurniawati; Faizah Faizah; Nurul Latifasari (Indonesian Journal of Community Service and Innovation (IJCOSIN), 2023)
Dage is a popular processed product in Banyumas, made from fermented coconut or soybean pulp using Rhizopus sp. There are still several challenges regarding standard procedures due to a need for knowledge about food safety and hygiene in production. The socialization of Good Manufacturing Practices (GMP) aims to enhance the knowledge and understanding of dance producers about proper food production. In the Ciberung Village, socialization and education about GMP were conducted for micro, small, and medium enterprises (MSMEs) involved in a stage production. The methods used included surveys, presentations, and discussions. The activities began with an observation and interview to identify problems in dage production. Then, a presentation on GMP was delivered by a speaker from Institut Teknologi Telkom Purwokerto. Subsequently, a discussion was conducted to ensure the producers understood the presented material. This activity's results indicated that the dage production in Ciberung Village did not meet GMP standards. The problem identification revealed uncertainties in the production outcomes due to a lack of standard production processes. The socialization of GMP is crucial to improve the production process, enhance product quality, and increasing the producer's productivity. It is expected that through this education, the quality of dage products will improve and meet food safety standards